(untitled) (Journal of the College of Basic Education, 2022)
The current research dealt with the possibility of studying folk art techniques as they constitute an important aspect in the completion of works of art, and the era after the Second World War witnessed remarkable transformations in the plastic structure and in the techniques of display and performance, and these techniques paved the way for the derivation of many raw materials due to the technological and industrial progress that coincided with those catch him. The research included four chapters, the first chapter of which came with the research problem, which was summarized in the following questions: 1. What are the limits of the folk art artist’s reliance on reality as an aesthetic source? What is the size of artistic creativity in the production of a transferred work of art? 2. Are the technical characteristics of folk art reflected in the productions of the students of the Department of Art Education?